Price discovery and basis risk for live hogs - Ted C Schroeder; B K Goodwin (Kansas Agricultural Experiment Station Research Reports, 1990)
The short- and long-run daily price relationships between cash and futures markets for live hogs were examined over the 1975-89 period. Price discovery generally originates in the futures market with about 65% of new information being passed from the futures to the cash market. However, at times, especially during large price moves that are not necessarily anticipated in the futures market, the cash market price relies less on the futures market. The very short-term basis for hogs is fairly stable, with approximately 85% of yesterday's nearby-basis persisting today. Generally, little can be gained by speculating on basis from day to day. The farther from futures contract delivery they are, the more the futures and cash price diverge from each other, reflecting the fact that they represent different markets. Hedgers liquidating futures positions prior to the contract delivery month face larger basis risk than those liquidating positions in the contract month.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; Marketing; Economics; Contract